PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIORAMA TERBUAT DARI KARTON DAN KARDUS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SEKOLAH DASAR NEGERI HINDU 4 BATUAN KABUPATEN GIANYAR - Ni Putu Sri Santi; I Made Wiguna Yasa; Ni Nyoman Suastini (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This study aims to analyze how the use of diorama media significantly affects the learning outcomes of fourth-grade students at SDN Hindu 4 Batuan. The subjectts of thist research were fourth-grade students at SDN Hindu 4 Batuan, Gianyar Regency. Data collection methods used in this study included tests and document analysis. The collected data were analyzed using normality tests and hypothesis testing with the Paired Sample T-test formula. The researcth findings showeed that tthe hypothesis testing using the Paired Sample T-teest on the pretest and posttest conducted in the fourth-grade class yielded a Sig. (2-taailed) value of 0.000 < 0.05. This result indicates that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that there is a significant influence of using diorama media on student learning outcomes in the IPAS subject, specifically on the topic of photosynthesis in the fourth grade at SDN Hindu 4 Batuan, Gianyar Regency.